ANALISIS KETIMPANGAN PENDAPATAN DAN IDENTIFIKASI SEKTOR BASIS ANTAR KECAMATAN DI KABUPATEN WONOGIRI TAHUN 2010-2014 - Pamrihnan, Alit; Cahyadin, Malik (EP FEB UNS, 2016)
This study aims to determine the level of inequality and base economic of Wonogiri Districts in 2010-2014. This study uses secondary data involve Gross Regional Domestic Product (GRDP) at Constant Price of 2000, GRDP per capita, Population and Economic Growth. The analytical method uses analysis of Williamson Index, Theil Entropy Index, Static Location Quotient (SLQ) and Dynamic Location Quotient (DLQ).Research results show that the Williamson Index of Wonogiri District tends to decrease, the higest level of income inequality happened in the Wonogiri Subdistric and the lowest level of income inequality happened in the Eromoko Subdistric. Entropy Theil index shows that inequality between subdistrict in Wonogiri District tends to decrease. Karangtengah Subdistrict has the higest income inequality while the lowest inequality is the Purwatoro Subdistrict. The Composite of LQ (SLQ dan DLQ) shows that the Agricultural Sector; Electricity, Gas and Water; Trade and Communication became base sector.Suggestions from this study cover the government of Wonogiri District is expected to improve infrastructures such as road, bridge, irrigation canal, and communication network. In addition, the Government of Wonogiri District should develop the potency of economy in each of subdistricts. Keywords: Income Inequality, Base Sector, Non Base SectorJEL: R11, R12